1995
DOI: 10.1128/aem.61.4.1555-1562.1995
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of the bacterial community from a microbial mat at an active, hydrothermal vent system, Loihi Seamount, Hawaii

Abstract: The phylogenetic diversity of small-subunit rRNA genes associated with the domain Bacteria was examined (by using previously defined operational taxonomic units [C. L. Moyer, F. C. Dobbs, and D. M. Karl, Appl. Environ. Microbiol. 60:871-879, 1994]; those for Pele's Vents Bacteria are hereafter abbreviated PVB OTUs) with samples from a microbial mat at an active, deep-sea hydrothermal vent system. A cluster of phylogenetically related PVB OTUs (OTUs 2, 3, 6, and 8) was closely affiliated with Thiovulum sp. cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(172 citation statements)
references
References 51 publications
9
162
0
1
Order By: Relevance
“…Notably absent from our clone libraries were sequences retrieved from GB hydrothermal deposits, chimneys and sediments (Teske et al, 2002;Dhillon et al, 2005;Pagé et al, 2008). In addition, only three sequences clustering with Epsilonproteobacteria were found; this group is typically abundant in deep-sea hydrothermal vent environments (Haddad et al, 1995;Moyer et al, 1995;Reysenbach et al, 2000;Corre et al, 2001;Longnecker and Reysenbach, 2001;Campbell et al, 2006) (Fig. 3C).…”
Section: Cultivation-independent Analysis Of Microbial Diversitymentioning
confidence: 88%
“…Notably absent from our clone libraries were sequences retrieved from GB hydrothermal deposits, chimneys and sediments (Teske et al, 2002;Dhillon et al, 2005;Pagé et al, 2008). In addition, only three sequences clustering with Epsilonproteobacteria were found; this group is typically abundant in deep-sea hydrothermal vent environments (Haddad et al, 1995;Moyer et al, 1995;Reysenbach et al, 2000;Corre et al, 2001;Longnecker and Reysenbach, 2001;Campbell et al, 2006) (Fig. 3C).…”
Section: Cultivation-independent Analysis Of Microbial Diversitymentioning
confidence: 88%
“…Molecular studies show the O-proteobacteria to be widespread at deep-sea hydrothermal vents associated with microbial mats [43,44,69], the vent polychete Alvinella pompejana [70,71], the vent worm Riftia pachyptila [72], and an in situ growth chamber with warm £uids [47,73]. Recently, the ¢rst representatives of this group were cultured and found to exhibit both heterotrophic and autotrophic sulfur reduction, moderate thermophily, and the ability to use hydrogen as an electron donor [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Twentyfour of these clones were most closely related (92^98%) to an uncultured bacterium, clone S17sBac16, from a hydrothermal vent microbial mat on the Southern East Paci¢c Rise [43]. Other clones in the O-proteobacteria from Marker 33 were related to uncultivated marine bacterium, including clones from a deep-sea cold seep in the Japan Trench [40], a hydrothermal microbial mat [44], deep-sea sediments [45,46], a growth chamber associated with warm hydrothermal £uids [18,47], an ectosymbiont of the hydrothermal vent shrimp Rimicaris [48], and methane seep tubeworm endosymbionts [49]. Some of the clones from Marker 33 were also related to cultured O-proteobacteria, such as Thiomicrospira denitri¢cans [50], Arcobacter spp.…”
Section: The O-proteobacteria Groupmentioning
confidence: 99%
“…Some members of these communities have previously been characterized using culturedependent and light-and electron-microscopy methods, and the presence of the filamentous sulfur-oxidizing bacteria Beggiatoa sp., Thioploca sp., Leucothrix, Thiotrix and Desmanthos has been confirmed [2,[10][11][12]. Other studies performed, using culture-independent techniques, have shown that microbial mat communities in vent or cold seep environments can be quite diverse and include prokaryotes such as Epsilonproteobacteria [13,14] or even Archaea [15], that are responsible for the filamentous structure of the mats. These organisms are thought to participate in either sulfide-or methanebased chemoautotrophy.…”
Section: Introductionmentioning
confidence: 93%